Tele-dentistry and Data Science: Enhancing Access and Quality of Dental Care - Sai Krupa, Chinthakunta (Journal of Science & Technology, 2024)
Tele-dentistry, coupled with data science techniques, presents a transformative approach to revolutionize dental care delivery, particularly in enhancing accessibility and quality. This paper investigates the synergistic potential of tele-dentistry and data science in enabling remote consultations, diagnostics, treatment planning, and patient monitoring. By leveraging digital technologies and advanced analytics, tele-dentistry extends dental services beyond traditional clinic settings, overcoming geographical barriers and improving healthcare outcomes. Key areas explored include teledentistry platforms, data-driven decision-making, artificial intelligence in diagnostics, patient engagement strategies, and regulatory considerations. Through a comprehensive analysis, this paper underscores the pivotal role of tele-dentistry and data science in addressing disparities in dental care access and advancing the standard of oral healthcare provision.
Keywords: Tele-dentistry; Data Science; Dental Care; Remote Consultations; Diagnostics; Treatment Planning; Patient Monitoring; Digital Technologies; Artificial Intelligence; Healthcare Access